ПРОБЛЕМНІ АСПЕКТИ НАДАННЯ БЕЗОПЛАТНОЇ ВТОРИННОЇ ПРАВОВОЇ ДОПОМОГИ В ЗАКОНОДАВСТВІ УКРАЇНИ ТА ПЕРСПЕКТИВИ ЇХ ВИРІШЕННЯ - Рибалкін, Андрій Олександрович, Зєлєніна Марина Володимирівна (SUPREMANCE OF LAW, 2019)
The article provides a comprehensive analysis of the institute of free secondary legal aid in Ukraine and formulates scientific and theoretical proposals for solving the problem aspects of its provision. It is emphasised that the quality of free legal aid depends on many factors. It is stressed that it is necessary to stimulate lawyers to provide qualitative assistance, since a significant number of cases, which an attorney has, disturbs concentration, and as a consequence, reduces the level of positive decisions. It is noted that free legal aid does not provide for the support of citizens in applying to international judicial bodies, for example, to the European Court of Human Rights. International assistance can be provided by the system of public receptions of the Ukrainian Helsinki Human Rights Union. It is emphasised that under the current conditions in Ukraine, the state and public organizations are actively working to increase the level of access to free legal aid in Ukraine. The Law of Ukraine “On Free Legal Aid” contains an expanded list of persons entitled, in particular, to receive free secondary legal aid, the rights and obligations of the subjects providing such assistance. However, given the abstract nature of the legal norms and the style of their presentation, there is a need in society for clarifying these normative provisions to the population. For this purpose, various activities are carried out, in particular, cooperation with the media, publishing of brochures, distribution of educational content on the Internet, which has a positive effect and, as a consequence, leads to the achievement of the corresponding goal -increasing of the level of accessibility of free legal aid in Ukraine.
Keywords: system of free legal aid; legal aid bureau; availability of free secondary legal aid; independence of the system of free legal aid